Surgical Wound Infection in Tinea Cruris - Atfi, Ismi Mulya (Journal of Midwifery, 2023)
Changes in the immune response during pregnancy until postpartum cause an increased risk of infection during pregnancy, including skin infections. Tinea cruris is a dermatophyte infection of the inguinal folds, inner thighs, perineum and buttocks. One of the risk factors for tinea cruris is obesity. Obesity aggravates the condition, causing skin changes and conditions (inflammatory and hypertrophic-based) that are often associated with excessive fungal or bacterial growth. Obesity is a risk factor for infection in Caesarean wounds. This case study will describe a patient who experienced an infected Caesarean wound with tinea cruris